Eating together and eating alone: meal arrangements in British households. (18th November 2016) - Yates, Luke; Warde, Alan
Abstract : Sociology traditionally accounts for eating in terms of the social organization of meals, their provision and consumption. A recurrent public concern is that the meal is being subverted. This paper examines meal arrangements in British households in 2012, drawing on an online survey in the format of a food diary administered to 2784 members of a supermarket consumer panel. It charts the organization of contemporary eating occasions, paying attention to socio‐demographic variation in practice. Especially, it explores companionless meals, putting them in contexts of food provisioning and temporal rhythms. Findings show that eating alone is associated with simpler, quicker meals, and that it takes place most commonly in the morning and midday. Those living alone eat alone more often, but at similar meal times, and they take longer over their lone meals. Comparison with a similar study in 1955–6 suggests some fragmentation or relaxation in collective schedules. The implications are not straightforward, and the causes probably lie more in institutional shifts than personal preferences. Declining levels of commensality are, however, associated with a reduction in household size and, especially in households with children, difficulties of coordinating family members' schedules.